Effect of ridge preservation at molar extraction sites with severe periodontitis on the Schneiderian membrane thickness changes: a pilot study - Yiping Wei; Bo Zhang; Gang Yang; Tao Xu; Wenjie Hu; Kwok-Hung Chung (BMC Oral Health, 2021)
Abstract Background Information regarding the reaction of bone augmentation in terms to sinus mucosa thickness of periodontally compromised molar extraction sites is limited. This retrospective study aimed to analyze the effect of ridge preservation procedures following the extraction of molars with severe periodontitis on the healing pattern of adjacent maxillary sinus mucosal membranes. Methods Thirty-one periodontally compromised maxillary molar teeth either receiving ridge preservation (test group, n = 20) or undergoing spontaneous healing (control group, n = 11) were investigated. Cone-beam computed tomography (CBCT) scanning was performed before the extraction procedure and repeated 6 months later. The mucosa thickness (MT) of the adjacent periodontally compromised molar tooth was measured from CBCT images before tooth extraction and after 6 months of healing at nine assigned measurement points. The data were analyzed at α = 0.05. Results The prevalence of pre-extraction maxillary sinus mucosal thickening was 60.0% and 63.6% in the test and control groups, respectively. The average MT of the thickened sinus mucosa before tooth extraction was 3.78 ± 2.36 mm in the test group and 4.63 ± 3.20 mm in the control group (P = 0.063). The mean mucosal thickening reductions in the thickened MT subjects after 6 months of healing were 2.20 ± 2.05 mm (test group) and 2.64 ± 2.70 mm (control group), P = 0.289. The differences of MT between the time prior to extraction and after 6 months of healing were statistically significant within both groups (P < 0.05). Conclusions Following extraction of molars with severe periodontitis, a reduction in swelling of the Schneiderian membrane has been observed regardless of the addition of a DBBM socket graft. However, a mucosal thickness > 2 mm was still frequently observed.